Perencanaan Pondasi Borepile Pada Jembatan, Studi Kasus : Jembatan Utama Cisadane - Wulan, Asri; Pujiawati, Krismonika; Kusumaningrum, Jennie (Jurnal Sains dan Teknologi (JSIT), 2023)
The most important part in a bridge construction is the foundation. Bore pile foundation is planned for 2 abutments and 5 piers. The entire foundation uses a diameter of 1 meter with a depth of 20-30 meters. Calculation of axial bearing capacity using the reese and wright method produces a single pile axial bearing capacity of 268.090 - 470.697 tons. The efficiency of the pile group using the Converse-Labarre method and the axial bearing capacity of the pile group is 5870,246 - 33176,233 tons. Single pile settlement using a semi-empirical method and resulted in a decrease of 50,100 - 59,490 mm. The settlement of the pile group used the vesic method and resulted in a decrease of 6,627 - 13,302 cm. consolidation decrease using the coefficient of volume change and resulted in a decrease of 104,024-576.047 mm with a time of 5,694-26,731 years. The calculation of lateral bearing capacity and pile deflection using the Broms method resulted in the lateral bearing capacity of the pile group of 3024-20580 tons and deflection of 1.485-5.888 mm. foundation reinforcement using the reference of SNI 2847-2019. Longitudinal reinforcement using 10D32 and stirrup reinforcement D16-50 and D16-75. Pile cap planning refers to SNI 2847-2019, resulting in a pile cap thickness of 1.5-4 meters. The X direction and Y direction reinforcement used are D32-150 for the pier and D32-150 and D25-150 for the abutment. The calculation of the cost budget plan uses the unit price analysis method and the resulting total cost is 73.574.031.053.